Association between daily salt intake of 3‐year‐old children and that of their mothers: A cross‐sectional study. Issue 4 (30th March 2018) - Takada, Toshihiko; Fukuma, Shingo; Shimizu, Sayaka; Hayashi, Michio; Miyashita, Jun; Azuma, Teruhisa; Fukuhara, Shunichi
Abstract: This study investigated the association between the daily salt intake of 3‐year‐old children and that of their mothers. A total of 641 children were studied. The daily salt intake of the children and their mothers was estimated by morning and spot urine methods, respectively. In the multivariable analysis, a 1 g higher maternal daily salt intake was associated with a 0.14 g (95% confidence interval [CI], 0.07‐0.22, P < .001) higher salt intake of her children. In the secondary analysis, the odds ratios for excess salt intake of children were 1.61 (95% CI, 1.01‐2.55, P = .045) and 1.81 (95% CI, 1.12‐2.91, P = .015) for 9.7‐11.5 g and 11.5 g or more of maternal daily salt intake, respectively. Our findings could help to convince mothers of the importance of appropriate salt intake, not only for themselves but also for their children.